Press-ekspress . Press-ekspress . Press Express . Пресс-экспресс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the live broadcast conversation between Alexandr Rutskoi and "Komsomolskaya Pravda" readers; press issues in independent Ukraine; church publications by Russian émigrés. Featured in the program: Rutskoi, Aleksandr Vladimirovich (Vice President of the Russian Federation); Fronin, Aleksandr (Chief Editor of "Komsomolskaya Pravda"); Dolganov, Vadim (Press Attaché of the Ukrainian Embassy) Contributors: Egorshev, Andrei (Anchor) Series description: Press reviews, interviews with journalists, presentations of magazines and newspapers. Об участии Александра Руцкого в прямой линии с читателями газеты"Комсомольская правда"; о прессе независимой Украины; о церковных изданиях русских эмигрантов. В программе участвуют: Руцкой, Александр Владимирович (Вице-президент Российской Федерации); Фронин, Александр (Главный редактор "Комсомольской правды"); Долганов, Вадим (Пресс-атташе посольства Украины) Создатели: Егоршев, Андрей (Ведущий/Ведущая) Описание серии: Обзор прессы, интервью с журналистами, представление журналов и газет.